1994
DOI: 10.1093/clinchem/40.5.777
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of liquid-chromatographic analysis of effusions for hyaluronate content

Abstract: A previously described HPLC method for determining hyaluronate in effusions was used to analyze a consecutive series of effusions from 1039 patients with pleural fluids and from 571 patients with peritoneal fluids. A mesothelioma was verified histologically in 50 of the cases. The results were used to estimate the clinical utility of the analysis. With a cutoff of 75 mg/L for hyaluronate-derived uronic acid, assay specificity for a malignant mesothelioma was 100% and the sensitivity 56%. Only 20% of the effusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…Effusions represent a major diagnostic challenge in clinical cytology and a combination of microscopic morphological evaluation and immunocytochemical staining is often necessary for an adequate diagnosis. [1][2][3] In our laboratory, we also use hyaluronan content to distinguish mesotheliomas from metastatic tumors and from benign mesothelial cells, 3,4 but around 10% of the effusions still remain unsolved, which is in agreement with other studies. 5,6 The spectrum of underlying diseases in the diagnostically refractory effusions differs considerably from those in unselected effusions and the samples may even lack diagnostic cells.…”
supporting
confidence: 87%
“…Effusions represent a major diagnostic challenge in clinical cytology and a combination of microscopic morphological evaluation and immunocytochemical staining is often necessary for an adequate diagnosis. [1][2][3] In our laboratory, we also use hyaluronan content to distinguish mesotheliomas from metastatic tumors and from benign mesothelial cells, 3,4 but around 10% of the effusions still remain unsolved, which is in agreement with other studies. 5,6 The spectrum of underlying diseases in the diagnostically refractory effusions differs considerably from those in unselected effusions and the samples may even lack diagnostic cells.…”
supporting
confidence: 87%
“…The peaks obtained at 231 nm were recorded and compared with the peaks obtained for external standards. 16 In a previous study, we have shown that values exceeding 75 mg/l of hyaluronan-derived uronic acid are specific for a mesothelioma. The probability of a mesothelioma is highly increased also in effusions with values higher than 25 mg/l but the specificity then is reduced to 95%.…”
Section: Methodsmentioning
confidence: 88%
“…14,15 A high-performance liquid chromatography (HPLC)-based method developed by Hjerpe and coworkers has proved to be specific enough and sensitive enough for routine diagnostic purposes, also in long-time use. 16 This analysis has the potential to identify a mesothelioma also in those cases where no diagnostic cells are shed into the effusion.…”
mentioning
confidence: 99%
“…Our findings supported the notion that the concentration of HA in malignant pleural effusion caused by MM is significantly higher than that in malignant pleural effusions associated with ACAs. 31,32 In many early studies on cell-cell aggregation, HA was found to mediate cross-linking of cells. Such cross-bridging suggests the existence of membrane-localized HA binding sites.…”
Section: Discussionmentioning
confidence: 99%